ISOLASI DAN KARAKTERISASI RHIZOBAKTERI POTENSIAL DARI ULTISOL SEBAGAI PUPUK HAYATI LOKAL - G Garuda (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Southeast Sulawesi is one of the provinces where agriculture is one of the fastest growing industries because most of the people are farmers. An obstacle encountered by farmers in Southeast Sulawesi is the lack of land for farming because most of the area is dominated by Ultisol. One way to overcome this problem is by using biofertilizers. This study aimed to isolate and characterize rhizobacteria from Ultisol as a material for making biofertilizers. The method used in sampling was purposive sampling. Soil samples taken were isolated for microorganisms and tested for hypersensitivity and then characterized based on the ability of nitrogen fixation, phosphate dissolving, and production of growth regulators. The test results and characterization of rhizobacteria selected 10 isolates from 92 isolated isolates, namely MN-06, MN-12, MN-21, KDI-09, KDI-11, KNW-02, KNW-05, KTM-07, KLK-04 , and KLK-09.